THE EFFECTIVENESS OF USING ENGLISH CONVERSATION APPLICATION TO IMPROVE THE STUDENTS’ SPEAKING SKILL AT THE SECOND SEMESTER OF PUBLIC ADMINISTRASION DEPARTMENT - Helmi (Universitas Achmad Yani Banjarmasin, 2020)
This research is an experimental research that was conducted by using English conversation applicatioon as a media to activate the students’ speaking skill of Public Administration Department. Speaking is one of the language skills to develop the communication competency, and to reach the level of functional literacy. Thus, speaking is one of the language skills that must be mastered by students. Based on those conditions, the writer tries to offer one teaching media for teaching speaking that is English conversation application. The purpose of this research was to know whether or not there was a significant effect of using English conversation application on the second semester at public administration department. The research design was quasi experimental research with non-equivalent groups pre-test and post-test design. Researcher chose two classes, they were given a pre-test to check on the equivalent of the groups on the dependent variable before the experiment began. After knowing the scores of pre-test the experimental group received treatment, that is, using guessing games while the control group was taught using question and answer technique. After that, the researcher gave a post-test to both groups to know the significant difference of the speaking achievement between the experimental and the control group. The subjects of this research were banjarmasin and banjarbaru class. Based on the computation of the t-test formula (from the scores of pre test), it showed that the mean scores of the control class was 54.28 and the mean scores of experimental class was 60.16. Meanwhile, the computation of the independent sample t-test formula (from the scores of post test) showed that the mean scores of control class was 52.78 and the mean scores of the experimental class was 61,02. Analyzing the mean scores of both groups, the mean scores of the students’ speaking test in the control class was decreased, from 54,28 to 52,78. On the contrary, the mean scores of the students’ speaking test in the experimental class was increased, from 60.16 to 61.02. From the fact findings, it can be seen that the treatment could give a significant result to the students’ speaking skill to the experimental class.